2018
DOI: 10.7150/jca.25005
|View full text |Cite
|
Sign up to set email alerts
|

CIP2A Promotes Proliferation, Invasion and Chemoresistance to Cisplatin in Renal Cell Carcinoma

Abstract: CIP2A is a well-known oncoprotein whose expression is elevated in multiple human solid tumor types. However, its role in renal cell carcinoma (RCC) development is poorly understood. Thus, in our present study, we used the renal cancer cell lines 786-O, A498 and CAKI-1 and the renal epithelial cell line HK-2 to clarify the function of CIP2A in RCC. We found that CIP2A expression is much higher in the RCC cells than in the normal renal epithelial cell. Lentivirus covered coding region CIP2A cDNA sequence and CIP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 32 publications
(37 reference statements)
0
21
0
Order By: Relevance
“…Even if a working concentration in the low micromolar or nanomolar range is usually considered more favorable, we report here that such concentrations of RS-F3 are not toxic against the healthy cell models tested. Moreover, the working concentration of this new drug is comparable to those commonly used for the well-known chemotherapeutic agent cisplatin in cellular studies [47,48,49]. Other approved anticancer drugs, such as carboplatin, cyclophosphamide, bleomycin, or the histone deacetylase (HDAC) inhibitor Belinostat, are used at maximum plasma concentrations in the high micromolar range [50].…”
Section: Discussionmentioning
confidence: 99%
“…Even if a working concentration in the low micromolar or nanomolar range is usually considered more favorable, we report here that such concentrations of RS-F3 are not toxic against the healthy cell models tested. Moreover, the working concentration of this new drug is comparable to those commonly used for the well-known chemotherapeutic agent cisplatin in cellular studies [47,48,49]. Other approved anticancer drugs, such as carboplatin, cyclophosphamide, bleomycin, or the histone deacetylase (HDAC) inhibitor Belinostat, are used at maximum plasma concentrations in the high micromolar range [50].…”
Section: Discussionmentioning
confidence: 99%
“…Cisplatin (DDP) has been used for ccRCC treatment [27,28,[30][31][32], but DDP-resistance generated by the RCC cells seriously limits the therapeutic efficacy of this drug in clinic. Recent data suggested that targeting the cancer associated genes was proved as novel strategies to improve drug sensitivity [8][9][10][11][12], but the role of CXCR4 in regulating cisplatin-sensitivity has not been investigated.…”
Section: Cxcr4 Regulated Ddp-sensitivity In Ccrcc Cells In Vitromentioning
confidence: 99%
“…Generation of drug resistance has become a serious obstacle to degrade the therapeutic efficacy of current chemical drugs for ccRCC treatment in clinic, such as cisplatin (DDP) [27][28][29]. According to the existed information, DDP-other types of treatments (other chemical drugs, radiotherapies, and immunotherapies) combined treatment strategies have been used for ccRCC treatment [27,28,[30][31][32]. Unfortunately, researchers notice that aberrant expressions of some cancer-associated genes contribute to DDP-resistance in ccRCC treatment, and targeting the corresponding genes, including CIP2A [30], SMYD2 [28], and PARK7 [27], improve DDP-sensitivity in ccRCC cells.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is because, upon downregulation of TRIM24, a decrease is observed in the proliferation, colony formation, and invasion of PCa cells [ 82 ]. Protein phosphatase 2A (CIP2A) is another oncogene factor participating in the malignancy of cancer cells and enhancing their growth and proliferation [ 83 , 84 ]. It was demonstrated that PCa cells elevate the expression of CIP2A to ensure their proliferation and malignancy [ 85 , 86 ].…”
Section: Sirna Targets Signaling Pathways: Focus On Pca Therapymentioning
confidence: 99%